Compact dual-band antennas with large frequency ratio and bandwidth enhancement for wireless applications - Boukarkar, Abdelheq; Lin, Xian Qi; Jiang, Yuan (International journal of microwave and wireless technologies, 2017)
In this paper, compact single-feed dual-band antennas for different wireless applications are proposed. First, a dual-band antenna with a comparatively large frequency ratio of 2.58 is designed. Then, a novel dual-band antenna is introduced in order to enhance the upper frequency band. The technique consists of modifying the feed line structure, which leads to a 9.23% of impedance bandwidth at the central frequency of 6.5 GHz instead of 2.06%. The designed antennas are fabricated and tested in the laboratory and in a small anechoic chamber in order to measure their reflection coefficient, gains, and efficiencies. Good agreement between simulated and measured results is obtained. The designed antennas are particular because they have low profile, very simple single-feed technique, can be designed for large frequency ratios, and also the bandwidth can be clearly enhanced. Therefore, they can be used for different wireless applications.